Validity and Reliability of Anxiety Sensitivity Index-3 (ASI-3) Indonesian Version In Clinical and Non-Clinical Samples - Fathiya Aisha Sadf; Hery Susanto (Psikostudia : Jurnal Psikologi, 2024)
Anxiety Sensitivity refers to an individual’s fear of anxiety-related sensations. Anxiety Sensitivity Index-3 (ASI-3) is the latest instrument used to measure anxiety sensitivity. So far, there hasn't been any investigation into the psychometric qualities of the Indonesian version of ASI-3. The aims of this rsearch is to to explore the psychometric characteristics of the ASI-3 instrument in Indonesian. Participants in this research were 264 individuals aged 18–54 years (M=23.86, SD=4.61) in Indonesia recruited through convenience sampling. The outcomes of the psychometric assessment using Confirmatory Factor Analysis (CFA), tests for construct validity, and Cronbach’s Alpha coefficient, indicated strong validity and reliability of the ASI-3. This study found the Indonesian version of ASI-3 has a similar theoretical model to the English version. Concluded that the Indonesian version of ASI-3 is a reliable instrument can be used as an adequate measure of anxiety sensitivity in Indonesia. The Indonesian version of ASI-3 can differentiate scores between individuals with and without psychological disorders.Sensitivitas Kecemasan (Anxiety Sensitivity) merupakan rasa takut individu akan sensasi yang timbul terkait kecemasan. Anxiety Sensitivity Index-3 (ASI-3) merupakan alat ukur baru yang digunakan untuk menilai sensitivitas kecemasan, namun belum ada riset yang mengkaji kualitas psikometrik adaptasi alat ukur dan uji psikomerik ASI-3 bahasa Indonesia. Penelitian ini bertujuan untuk mengeksplorasi karakteristik psikometrik instrumen ASI-3 dalam bahasa Indonesia. Partisipan penelitian ini adalah 262 individu berusia 18–54 tahun (M=23.86, SD=4.61) di Indonesia yang dikumpulkan dengan convenience sampling. Hasil evaluasi psikometrik menggunakan analisis faktor konfirmatori (CFA), uji validitas konstruk, dan penghitungan Cronbach’s Alpha menunjukkan bahwa ASI-3 menunjukkan tingkat validitas dan reliabilitas yang signifikan, serta mengadopsi model teoretis yang serupa dengan versi bahasa Inggrisnya. Penelitian ini menyimpulkan bahwa ASI-3 layak digunakan sebagai alat ukur yang efektif untuk menilai tingkat sensitivitas terhadap kecemasan di Indonesia. ASI-3 versi bahasa Indonesia dapat membedakan skor antara individu dengan gangguan psikologis dan individu tanpa gangguan psikologis.